THE ROLE OF INTERCULTURAL COMPETENCE IN FOREIGN LANGUAGE TEACHING: THE ROLE OF INTERCULTURAL COMPETENCE IN FOREIGN LANGUAGE - B.A.Arzieva, B.A.Arzieva (Журнал иностранных языков и лингвистики, 2025)
The Decree of the President of the Republic of Uzbekistan Shavkat Mirziyoyev "On the Development Strategy of Uzbekistan" mentions cardinal improvement of the quality of general secondary education, promotion of in-depth study of foreign languages, informatics and other important and popular disciplines. However, teaching English in today's multicultural contexts requires more than just linguistic proficiency; it demands a nuanced understanding of diverse cultural norms, values, and communication styles. This realization underscores the significance of intercultural competence development among students in higher education institutions who aspire to become English language teachers.